Assessment of ozone and UV pre-oxidation processes for mitigating microbiologically accelerated monochloramine decay. Issue 1 (February 2018) - Moradi, Sina; Hancock, Sam; Chow, Christopher W.K.; Leeuwen, John van; Drikas, Mary; Harris, Martin; Cook, David; Amal, Rose
Graphical abstract: Highlights: Effects of preoxidation on chemical and microbial decay coefficients were assessed. UV was less effective than ozone in removing microbial decay factor in raw water. Employing ozone and UV did not affect chemical component of monochloramine decay. Correlations between 3D-FEEM spectroscopy and microbial decay factor were found. Pre-ozonation decreased marine humic-like and soluble microbial-like substances. Abstract: This paper reports the effects of pre-oxidation processes including ozone and ultraviolet (UV) irradiation prior to chloramination on microbiologically assisted monochloramine decay. Water samples with varying water qualities were pre-oxidated by ozone and UV irradiation, followed by determination of chemical and microbiological monochloramine decay ( F m ). Both ozone and UV could effectively improve the reduction of microbial-like compounds responsible for monochloramine decay in treated water samples. Reductions in F m values were observed for ozone contact times (Ct) greater than 5 mg min/L and UV doses greater than 30 mJ/cm 2 . However, UV was less effective than ozone in reducing F m values in raw water samples. Complete removal of the microbiological component of the decay for raw water samples was not found either with ozone (even with Ct of 50 mg min/L) or UV (even with UV dose of 120 mJ/cm 2 ). The effects of pre-oxidation processes on chemical (kc ) and microbial (km ) decay coefficients were assessed. Increasing both ozone Ct and UV dose ahead of chloramine did not affect the chemical decay component, but they changed the microbiological component of decay. Changes in organic matter after ozonation were also characterized using three-dimensional fluorescence excitation–emission matrix (3D-FEEM) spectroscopy, and correlations between 3D-FEEM spectroscopy results and F m values were found. Intensities of humic-like, fulvic-like, microbial protein-like and aromatic protein-like substances were reduced by pre-ozonation. Based on the 3D-FEEM results, we can confirm that the slowdown of monochloramine decay rate is due to the reduction of marine humic-like substances and soluble microbial protein-like compounds by pre-ozonation.